VISUAL SEMIOTICS STUDY IN SAUCE'S AXE-EFFECT ME CALL AD VERSION - Iman Sumargono; Muhammad Hidayattuloh (Balong International Journal of Design, 2020)
ABSTRACT Advertising entices with audio and visual displays that are packaged or engineered perfectly through shows that assemble everyday life, form opinions and social behavior, even have the ability to shape one's character and identity. Social statuses can be produced through advertisements that are distributed through print media, radio, television, film and the internet, distinguishing these statuses based on gender, class, race, or sex. In almost all displays of body care product advertisements, the cast (female) plays an important part in building the product image. The female model in the product advertisement depicts women with beauty who have depictions such as white, long hair, attractive appearance, tall, slender and are serving a variety of men's needs, especially in Axe ads. Based on the phenomena presented above, the researcher intends to analyze the Axe Effect Indonesia Ad-Sauce ad. contained in it with the aim to find out the symbols that will be captured from the ad and to explore the emergence factors of the image of sexuality in the Indonesian Axe Effect Indonesia Ad-Sauce Axe ad. Keywords: Axe Effect Indonesia Ad-Sauce, advertising strategy, sexuality imagery